Inequality : causes and consequences - Cappellari, Lorenzo; Polachek, S. W.; Tatsiramos, Konstantinos (Research in labor economics ;, 2016)
Research in Labor Economics volume 43 contains new and innovative research on the causes and consequences of inequality.